Pengaruh Literasi Keuangan, Pendapatan, dan Gaya Hidup terhadap Pengelolaan Keuangan Masyarakat di Desa Bukit Mulia, Tanah Laut - Putriana, Astia; Nor Rahma Rizka; Wigati Werdiningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This research investigates how financial literacy, income level, and lifestyle influence financial management practices among residents of Bukit Mulia Village, Tanah Laut Regency. Applying the Slovin formula yielded a sample size consisting of 100 household heads who served as the study’s respondents. Data collection was conducted through structured questionnaires, and the analysis employed hypothesis testing using SPSS 26. The analysis results indicate that financial literacy has an impact on financial management, while income and lifestyle show no meaningful influence. These results underscore the essential importance of financial literacy in enhancing individuals’ capacity to plan and manage their finances effectively. Consequently, it is highly recommended that financial education and training initiatives be implemented in Bukit Mulia Village to strengthen residents’ financial decision- making capacity and promote better household financial stability.